Comparative transcriptomic and lipidomic analyses indicate that cold stress enhanced the production of the long C18–C22 polyunsaturated fatty acids in Aurantiochytrium sp. - Song, Yingjie; Hu, Zhangli; Xiong, Zheng; Li, Shuangfei; Liu, Wei; Tian, Tian; Yang, Xuewei (Frontiers in Microbiology, 2022)
Aurantiochytrium sp. belonging to Thraustochytrids are known for their capacity to produce long-chain polyunsaturated fatty acids (PUFAs). However, effects of cold stress accompanied with staged-temperature control on the fatty acid metabolism in Aurantiochytrium sp. were rarely studied. In this study, cold stress (15°C, 5°C) was applied for Aurantiochytrium sp., with the physiological responses (morphology, growth, fatty acid profiling) and gene expression related FA synthesis, lipid metabolism, and regulatory processes was observed. Results showed that there is a significant change for the lipid types under 5°C (251 species) and 15°C (97 species) treatment. The 5°C treatment was benefit for the C18–C22 PUFAs with the yield of docosahexaenoic acid (DHA) increased to 1.25 times. After incubation at 15°C, the accumulation of eicosadienoic acid (EA) (20:2) was increased to 2.00-fold. Based on transcriptomic and qPCR analysis, an increase in genes involved in fatty acid synthase (FAS) and polyketide synthase (PKS) pathways was observed under low-temperature treatment. With upregulation of 3-ketoacyl-CoA synthase (2.44-fold), ketoreductase (2.50-fold), and dTDP-glucose 4,6-Dehydratase (rfbB) (2.31-fold) involved in PKS pathway, the accumulation of DHA was enhanced under 5°C. While, FAS and fatty elongase 3 (ELO) involved in the FAS pathway were upregulated (1.55-fold and 2.45-fold, respectively) to accumulate PUFAs at 15°C. Additionally, glycerol-3-phosphate acyltransferase (GPAT), lysophospholipid acyltransferase (LPAT), phosphatidic acid phosphatase (PAP), phosphatidylserine synthase (PSS), and phosphatidylserine decarboxylase (PSD) involved in glycerophospholipid biosynthesis were upregulated at 5°C increasing the accumulation of phosphatidic acid (PA), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol (PG), and phosphatidylinositol (PI). However, glycolysis and the TCA cycle were inhibited under 5°C. This study provides a contribution to the application of two-staged temperature control in the Aurantiochytrium sp. fermentation for producing cold stress-enhancing PUFAs, in order to better understand the function of the key genes for future genetic engineering.